Pharmacological evidence for β2-adrenoceptor in right atria from stressed female rats - Spadari-Bratfisch, R. C.; Santos, I. N.; Vanderlei, L. C M [UNESP]; Marcondes, F. K. (My University, 1999)
The purpose of the present study was to demonstrate a physiological response to TA2005, a potent β2-adrenoceptor (β2-AR) selective agonist, in right atria isolated from stressed female rats under the influence of the estrous cycle. We obtained concentration-response curves to the agonist in the presence and in the absence of selective antagonists in right atria isolated from female rats submitted to three daily foot-shock sessions (30 min duration, 120 pulses of 1.0 mA, 1.0 s, applied at random intervals of 5- 25 s) and sacrificed at estrus or diestrus. Our results showed that the pD2 values of TA2005 were not influenced by estrous cycle phase or foot-shock stress. However, in right atria from stressed rats sacrificed during diestins, the concentration-response curve to TA2005 was biphasic, with a response being obtained at concentrations of 0.1 nM, whereas during estrus no response was observed at doses lower than 3 nM. ICI118,551, a β2-AR antagonist, abolished the response to nanomolar concentrations of TA2005 in right atria from stressed rats at diestrus, with no changes in agonist pD2 values in right atria from control rats (7.47 ± 0.09, p > 0.05) but a 3-fold decrease in pD2 values of TA2005 in right atria from foot shock stressed rats (7.90 ± 0.07, p ≤ 0.05). Concentration-response curves to TA2005 in the presence of ICI118,551 were best fitted by a one-site model equation. The β1-AR antagonist, CGP20712A, shifted to the right only the second part of the concentration-response curves to the agonist, unmasking the putative β2-AR-mediated response to the agonist in tissues isolated from stressed rats at diestrus. Under this condition, concentration-response curves to the agonist were best fitted by a two-site model equation, pD2 and maximum response of TA2005 interaction with β1- and putative β2-adrenoceptor components were calculated. Schild analyses gave a pK(B) value for CGP20712A that was typical for the interaction with β1-AR in each experimental group, pK(B) values for ICI118,551 could not be obtained in stressed rats sacrificed at diestins since Schild plot slopes were lower than 1.0. In right atria from control rats, ICI118,551 pK(B) values were similar to reported values for the interaction of the antagonist with β1-AR. These results confirm that a heterogenous β1-AR population mediating the chronotropic response to catecholamines can be demonstrated in right atria from foot shock stressed female rats sacrificed at diestins. The stress-induced response seems to be mediated by the β2-AR subtype. Right atria from rats sacrificed during estrus are protected against stress-induced alterations on the homogeneity of β-AR population.
Keywords: CGP20712A; Diestrus; Estrus; Foot-shock stress; ICI118,551; TA2005; 3 isopropylamino 1 (7 methyl 4 indanyloxy) 2 butanol; 5 [2 [[2 hydroxy 3 [4 (1 methyl 4 trifluoromethyl 2 imidazolyl)phenoxy]propyl]amino]ethoxy]salicylamide; beta 2 adrenergic receptor; carmoterol; amphetamine derivative; imidazole derivative; propanolamine derivative; quinolinol derivative; quinolone derivative; animal experiment; animal tissue; controlled study; diestrus; estrus cycle; female; heart right atrium; nonhuman; priority journal; rat; shock; stress; animal; dose response; drug effect; estrus; heart atrium; heart rate; pathophysiology; physiology; Wistar rat; Amphetamines; Animals; Dose-Response Relationship, Drug; Female; Heart Atria; Heart Rate; Hydroxyquinolines; Imidazoles; Propanolamines; Quinolones; Rats; Rats, Wistar; Receptors, Adrenergic, beta-2; Stress